Estudo da difusão de hidrogênio em uma liga de alta entropia (CoCrFeNiMn) equimolar e nanocristalina - Belo, Jardel de Souza (2017)
Without a base element, High Entropy Alloys (HEA) have many crystallines structures and microstructures. HEA can have high wear resistance, high hardness, compressive strength at high temperatures and good resistance to corrosion. High Entropy Alloys can have a single phase or more phases. The alloys can show slow diffusion, stabilizing the microstructure thermally. The aim of the present project consists in evaluating the microstructural, mechanical properties and interaction and hydrogen’s diffusion with a polycrystalline and nanocrystalline HEA. The CoCrFeMnNi alloy was melt in an arc melt furnace, and then was annealed at 900°C, being, cold rolled 50% and 70% and submitted to High Pressure Process (HPT), in order to produce a nanocrystalline. Characterization techniques used were: X-ray diffraction, Scanning Electron Microscopy, Atomic Force Microscope, Hydrogen gas permeation and Thermal Desorption Spectroscopy. The alloy shows a single phase structure FCC, hardness average 170 HV, 376HV, 350 HV and 564 HV for annealed, cold rolling 50% and 70% and nanocrystalline respectively. For the first time was catalogued the hydrogen’s coefficient diffusion for this alloy, at 350 °C the coefficient is 9,3x10-12 m²/s for annealed and 8,3x10-12 m²/s for 50%, and 5,6x10-12 m²/s for nanocrystalline alloy at 300°C.